(untitled) (Symposium on Natural and Applied Sciences, 2026)
Such technologies are based on the idea of expanding and deepening traditional educational text through more advanced learning materials and replacing it by using courses and animated fragments. In this process, interconnected nodes are created between selected text fragments. According to specialists, hypertext imitates the ability of human intelligence to retain large amounts of information and to search within it through associative communication and thinking processes. In other words, hypertext is a complexly organized system of educational materials that incorporates a large amount of static and dynamic information and has a generalized network structure. Text, graphics, diagrams, video fragments, executable programs, and animations serve as information fragments. Texts, in turn, may consist of smaller texts nested within one another many times, like a “matryoshka” (a doll within a doll).